173k views
3 votes
Verify the following: 3

−21 × −4 + −6 = −21 × −4 + (−21) × (−6)​

User Lefty
by
6.1k points

2 Answers

2 votes

Answer:

the answer is -14 how about

study math next time

User ICrus
by
6.0k points
2 votes

Answer:

Incorrect

Explanation:

Use PEMDAS

Solve one side of the equation first

-21 × -4 + - 6

negative × negative = positive

84 + - 6

positive + negative = negative

84 - 6

78

Now solve the other side of the equation

-21 × -4 + (-21) × (-6)

negative × negative = positive

-21 × -4 + (126)

negative × negative = positive

84 + 126

210

Does 78 = 210?

No, so we can assume this equation is incorrect

User Geetanshu Gulati
by
5.3k points